Pengaruh Employer Attractiveness dan Ekspektasi Kerja Terhadap Minat Melamar Pekerjaan Mahasiswa - Dismas Persada Dewangga Pramudita; Ignatia Eka Puspita Kriswianti; Raden Agoeng Bhimasta (Forum Inovasi Bisnis dan Manajemen, 2024)
The expectations of today's young generation about the place where they work are certainly important to consider. To support this process, the interest of the workforce in applying for a job in the company is very important. Currently, companies are competing with each other to get the best prospective employees, the majority of whom are millennials. This study examines the perceptions of employer attractiveness and work expectations on the interest of students in applying for a job in management study program class of 2021. Employer attractiveness and work expectations are examined for their influence on interest in applying for a job. In this study, questionnaires were distributed online to collect data from respondents. The data collected was processed using the multiple linear regression analysis method, which was carried out using the help of the SPSS version 23 program. The results of this study indicate that perceptions of employer attractiveness and work expectations affect interest in applying for work positively.